Soil-Building Interaction under Surface Horizontal Strain Induced by Underground Mining - Xiaopeng Liu; Liangji Xu (Advances in Civil Engineering)
Underground mining causes the ground to deform, leading to the destruction of buildings. Horizontal strain is one of the most important causes of damage to strip foundation buildings. However, related research is insufficient and the mechanism behind building damage caused by horizontal strain remains unclear, resulting in several difficulties in performing coal mining under villages. In this study, interface slip and soil pressure caused by the horizontal strain of ground transfer between soil and buildings are investigated, and stress concentration in buildings driven by soil movement is considered the primary cause of building damage. The influences of the mechanical parameters of soil and the geometric parameters of a building on stress distribution inside a building are analyzed by establishing a stress distribution model of a building under different ground horizontal strains. Softening the foundation or designing deformation joints inside a building can reduce the influence of horizontal strain on a building. This research can provide an important reference for performing coal mining safely under villages and designing building protection against ground horizontal strain.